Confinement of Au3+-rich clusters by using Silicalite-1 for selective solvent-free oxidation of toluene. Issue 26 (2nd June 2021) - Huang, He; Ye, Wanyue; Song, Caicheng; Liu, Yingcen; Zhang, Xiaotong; Shan, Yu; Ge, Yuzhen; Zhang, Shufen; Lu, Rongwen
Abstract : Synergistic catalysis of Au 0 and Au 3+ dual active sites confined in Silicalite-1 for selective solvent-free oxidation of toluene to benzaldehyde with molecular oxygen. Abstract : The selective oxidation of primary carbon–hydrogen bonds in the methyl group of toluene to corresponding oxygenates is of immense significance. This transformation, however, remains challenging and often requires either extensive optimization of the present chemical operating processes or, more importantly, the design and development of novel catalysts. In this paper, we achieve the confinement of uniform Au nanoparticles by using Silicalite-1 (Au@Silicalite-1) via an improved impregnation method for solvent-free oxidation of toluene by oxygen to benzaldehyde. In situ Ar + etching XPS experiments revealed that in the evolution of Au 0 and Au 3+ species in a single Au@Silicalite-1 crystal the proportion of the Au 3+ species becomes enriched from 0 on the surface to >80% in the center. In the synergetic catalysis between Au 0 and Au 3+ species, it was observed that the electron-rich Au 0 species activated oxygen to form superoxide anion radicals, while the electron-deficient Au 3+ species promoted activation of the primary carbon–hydrogen bond in toluene and enabled efficient desorption of the desired product benzaldehyde with selectivity >90%. For comparison, Silicalite-1 or SiO2 supported Au 0 -rich catalysts exhibited strong adsorption of benzaldehyde, generating overoxidized benzoic acid as the main product.